1966
DOI: 10.1182/blood.v28.4.581.581
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Cytochemical Studies on Marrow Cells in B12 and Folate Deficiency

Abstract: In order to define the functional defect in marrow cells in B12 and folate deficiency, ten patients were investigated. Chromosome studies showed alterations similar to those produced experimentally by agents interfering with DNA metabolism. Measurements of the DNA content of individual cells in the resting and synthetic stages of the mitotic cycle suggested arrest of DNA synthesis in a proportion of cells, or alternatively prolongation of the S and G2 phases. It was concluded that in these deficiency states ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…In fact, with the exception of Case 5, who had the highest pre-treatment folatc level in this study, it appeared that the folate therapy further diminished the proportion of earlypolychromatic cells in DNA synthesis (Table IV). Since megaloblastic erythropoiesis due to folate deficiency is known to be associated with an arrest in DNA synthesis (Menzies et al, 1966), a possible explanation for this finding might be that folate deficiency is associated with some degree of depression in the rate ofDNA synthesis, and that this is accelerated by folate therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, with the exception of Case 5, who had the highest pre-treatment folatc level in this study, it appeared that the folate therapy further diminished the proportion of earlypolychromatic cells in DNA synthesis (Table IV). Since megaloblastic erythropoiesis due to folate deficiency is known to be associated with an arrest in DNA synthesis (Menzies et al, 1966), a possible explanation for this finding might be that folate deficiency is associated with some degree of depression in the rate ofDNA synthesis, and that this is accelerated by folate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This paper describes the results of a study of erythroblast proliferation in P-thalassaemia, using a combination of quantitative cytochemistry and autoradiography. The value of this technique in the detection of disturbances in cell proliferation has been established in previous studies of pernicious anaemia and sideroblastic anaemia (Menzies ct al, 1966;Bock et al, 1967;Yoshida et a/, 1968;Wickramasinghe et al, 1968a Wickramasinghe et al, , b, 1969.…”
mentioning
confidence: 95%
“…Folate deficiency during this critical period might then promote genetic damage. Folic acid deficiency has been associated with an increased frequency of chromosomal breaks, gaps, triradial and quadriradial forms, ring chromosomes, and despiralization in vitamin deficient patients and in human lymphocytes and CHO cells grown in low folate medium [Heath, 1966;Menzies, 1966;Das et al, 1986;Li et al, 1986;Chen et al, 1989;Libbus et al, 1990). These chromosome aberrations, except for the despiralization, resemble the chromosome damage caused by nucleotide precursor pool imbalances in cultured cells [Kunz, 1982;Meuth, 19841.…”
Section: Studies Of Nutritional Factorsmentioning
confidence: 99%
“…In the erythroblastic cell compartment of PA, studies have shown an increased number of cells with DNA values ranging around the 4c level and several cells with DNA values between 2c and 4c values, which did not participate in DNA synthesis as judged by ['HITdR labelling (Menzies et al, 1966; Wickramasinghe et a!, 1968;Yoshida et al, 1968). In our three cases of PA, besides the macrocytic anaemia there was also a striking thrombocytopenia (platelet counts of 40 000-60 ooo/pl).…”
Section: Pernicious Anaemiamentioning
confidence: 99%